2007
DOI: 10.1016/j.jacc.2007.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Perfusion Imaging at 3-Tesla for the Detection of Coronary Artery Disease

Abstract: Our study showed that 3-T CMR perfusion imaging is superior to 1.5-T for prediction of significant single- and multi-vessel coronary disease, and 3-T may become the preferred CMR field strength for myocardial perfusion assessment in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(129 citation statements)
references
References 25 publications
11
117
0
1
Order By: Relevance
“…Gadolinium chelates do not enter intact cell membranes and the volume of distribution is restricted to approximately 20% in normal viable myocardium (24). Different extravascular, extracellular contrast medium dose administration protocols and pulse sequences have been tested and validated in animal experiments (25)(26)(27), which have been subsequently translated into human studies (28)(29)(30)(31)(32)(33).…”
Section: Mbf Measurement: Recent Advances Cmrmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium chelates do not enter intact cell membranes and the volume of distribution is restricted to approximately 20% in normal viable myocardium (24). Different extravascular, extracellular contrast medium dose administration protocols and pulse sequences have been tested and validated in animal experiments (25)(26)(27), which have been subsequently translated into human studies (28)(29)(30)(31)(32)(33).…”
Section: Mbf Measurement: Recent Advances Cmrmentioning
confidence: 99%
“…On the other hand, increased field inhomogeneities can lead to more artifacts in perfusion imaging. In a pilot study in 65 patients, Cheng et al reported that 3-T CMR perfusion imaging provides an improved diagnostic accuracy, sensitivity, and specificity for the detection of significant coronary stenosis perfusion imaging (30). Pulse sequences to perform CMR perfusion at 3 T are commercially available, and it is conceivable that in the near future more data will be available to analyze the performance of higher-magnetic-field-strength systems on a large scale.…”
Section: Mbf Measurement: Recent Advances Cmrmentioning
confidence: 99%
“…The percentage of amino acid sequence homology of A 2A AR in the three species was determined to be as follows: human vs. rat 82 %, human vs. mouse 82 %, and rat vs. mouse 96 %. Adenosine (Adenoscan®) and regadenoson (Lexiscan®) are used in myocardial stress imaging acting on A 2A ARs of coronary blood vessels which leads to dilation and a drop in blood pressure [20,21]. The A 2A AR represents one of the most important regulators of the innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Während die Gewinnung funktioneller Parameter ähnliche Ergebnisse bei 1,5 und 3 T liefert [82,84], scheinen sich Vorteile von 3 T vor allem bei kontrastmittelunterstützten Techniken (Angiografien, Vitalitätsdiagnostik und Perfusion) abzuzeichnen. So konnte beispielsweise bei 3 T im direkten Patienten-und Feldstärkever-gleich eine erhöhte Sensitivität, Genauigkeit und Spezifizität der Adenosin-Stress-Perfusion zum Nachweis von hämodynamisch relevanten Koronarstenosen bei Verdacht auf koronare Herzkrankheit gefunden werden [85]. Dies wird jedoch in einer aktuellen Metaanalyse [86] drastisch relativiert.…”
Section: Tesla-mrt In Der Herzbildgebungunclassified